How can one own the sky? symposium on low-level flying above Innu land in Canada in connection with the 1993 UN-year for Indigenous Peoples - proceedings (Maastricht: University of Limburg, 1993)
"The symposium is organied by: Prof. mr B.V.A. Röling Dispute, facultary society for international and European justice university of Limburg and Foundation Innu Support Group."